Lingkungan Kerja, Stress Kerja Dan Disiplin Kerja Pengaruhnya Terhadap Prestasi Kerja Pegawai (Studi Pada Dinas Pendidikan Kabupaten Sorong - Malak, Welem (Universitas Sam Ratulangi, 2018)
The purpose of this study was determine to the effect of work environment, work stress and work discipline. This Research done in the education department staff of Kabupaten Sorong. This study used quantitative research models of associative. The results showed that the work environment and work discipline had significantly influence on work achievement, but work stress has a not significantly influence on work achievementKeywords: Work environment, work stress, work discipline, work achievement